Contextualising food waste prevention - Decisive moments within everyday practices. (10th February 2019) - Hebrok, Marie; Heidenstrøm, Nina
Abstract: Household food waste is a matter of increasing concern for policy makers and organisations because recent research has shown that consumers contribute to about half of the edible food wasted in the developed world. The most applied measure to address the problem has been knowledge and awareness campaigns aiming at inducing changes in behaviour by educating consumers of the scale and impact of food waste, and on the meaning of date labelling. We argue that this approach is insufficient in achieving food waste reduction on a satisfactory scale, and that the potential of implementing measures into the actual contexts of food waste related practices should be further explored and developed. The research presented in this article is based on fieldwork from 26 households in Oslo, Norway. By applying a practice-oriented approach to food waste drivers, we focus on five food waste related practices: acquiring, storing, assessing, valuing and eating. Based on our analysis of how these practices are causing food waste, we identify decisive moments and contexts for food waste prevention and discuss examples of measures that could be further explored. The aim is to inspire a more contextual approach to food waste prevention by policy makers and organisations. Highlights: Practices are food waste drivers: acquiring, storing, assessing, valuing, and eating. Decisive moments within practices represent opportunities for food waste prevention. Interventions should be developed as practice-oriented contextual measures. Calling for a more contextual approach to food waste prevention.